A case of significant weight loss and severe malnutrition caused by achalasia (Indian Journal of Case Reports, 2022)
Achalasia is caused by chronic degeneration of ganglionic cells in the myenteric plexus that leads to failure of relaxation of the lower esophageal sphincter (LES). This leads to aperistalsis of the digital esophagus and eventually led to dilation of the lower esophagus. We present the case of a 37-year-old man who initially presented with dysphagia for solid food and then slowly developed dysphagia for liquid over the past 6 months. He had significant weight loss, and his esophagogastroduodenoscopy (EGD) showed esophagitis and gastritis. The imaging of computed tomography (CT) with oral contrast showed dilation of the distal esophagus and mild circumferential thickening at the gastroesophageal junction. After the failure of response to BoTox-infiltration in the LES, the patient was taken for Heller’s myotomy. He showed immediate improvement in dysphagia after surgical intervention. This case study includes findings from CT scan, X-ray, and EGD with biopsies in this patient. This paper also summarizes the therapeutic options of BoTox-injection and surgical myotomy